Sukuk Defaults: On Distress Resolution in Islamic Finance - Sweder van Wijnbergen; Sajjad Zaheer (Tinbergen Institute, 2013)
Islamic strictures require investors to share risks with the entrepreneurs they finance. Sukuk (Islamic securities) come mostly in two varieties, musharakah (basically a joint venture agreement) and ijarah (more like an operational lease agreement). Yet defaults did happen, even in the case of musharakah (joint venture) sukuk discussed in this study. So is Islamic finance failing to deliver on its promises? To answer that question, we analyse four major defaults on Sukuk that have happened recently in the aftermath of the worldwide credit crisis that has engulfed the world since 2007. These case studies make clear that in most cases, the problems can be traced back to clauses and structures that made the sukuk more like conventional bonds. Furthermore, once default happened, most of the sukuk discussed did not transfer the underlying assets to the sukuk holders. So, in the event of default, due to limited recourse provisions, sukuk holders often had nothing to res ort to, as effectively there were no underlying assets in their ownership. The case studies highlighted the importance of the legal institutions of the country where the collateral is likely to be contested. Interestingly enough, strict adherence to shariah principles would have considerably simplified restructuring because shariah compliance implies a clear allocation of property rights: in sukuk, investors will receive full title to the underlying sukuk assets in distress situations. So the answer to the question we asked, is Islamic Finance failing to deliver on its promises, is a qualified no.
Keywords: G01; G15; G23; G33; P14; 330; Defaults; Islamic Securities; Islamic Finance